2016
DOI: 10.1016/j.pmedr.2015.12.006
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of the health benefits of Tai Chi for students in higher education

Abstract: BackgroundThe poor health consequences of stress are well recognized, and students in higher education may be at particular risk. Tai Chi integrates physical exercise with mindfulness techniques and seems well suited to relieve stress and related conditions.MethodsWe conducted a systematic review of the health benefits of Tai Chi for students in higher education reported in the English and Chinese literature, using an evidence hierarchy approach, allowing the inclusion of studies additional to randomized contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 40 publications
2
43
0
3
Order By: Relevance
“…Evidence exists in English and Chinese research literature for the beneficial effects of TCC on physical and mental health of college students 15. A recent meta-analysis found TCC to have a moderate effect on reducing anxiety symptoms (Hedges’ g =0.66; 95% confidence interval, 0.29–1.03), but the quality of the studies published in the literature is modest 16.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists in English and Chinese research literature for the beneficial effects of TCC on physical and mental health of college students 15. A recent meta-analysis found TCC to have a moderate effect on reducing anxiety symptoms (Hedges’ g =0.66; 95% confidence interval, 0.29–1.03), but the quality of the studies published in the literature is modest 16.…”
Section: Introductionmentioning
confidence: 99%
“…One potential reason that healthcare students experience higher levels of anxiety is likely due to the fact that the clinical tasks and practical skills of a healthcare provider are tested in oral or practical formats with openended questioning and these types of testing situations produce higher levels of anxiety compared to a multiple-choice type of examination [51]. Regardless of the specific cause for the increased anxiety, it stands to reason that finding ways to reduce anxiety in students is much needed in the educational setting given that anxiety can lead to both psychological and physiological changes [52] [53], can decrease immunity and when chronic in nature, anxiety can be a precursor to the development of hypertension and coronary heart disease [13] [20] found a significant reduction in heart rate in mental health patients following an interaction with a therapy dog, however there were no significant reductions in systolic or diastolic blood pressure. Braun et al [34] did not find a significant reduction in heart rate or blood pressure in children in an acute care pediatric setting following a 15 -20 minute animal-assisted intervention.…”
Section: Discussionmentioning
confidence: 99%
“…The concept of TCC training is considered to be able to improve dancer's body control and awareness. Research has reported that TCC training facilitates improving muscle strength and flexibility as well as balance and postural stability [3][4][5][6][7][8][9]. Lan et al found that TCC training increased knee extensor muscle strength and endurance [10].…”
Section: Several Dance Companies In Taiwan Have Introduced Tai Chimentioning
confidence: 99%
“…Lan et al found that TCC training increased knee extensor muscle strength and endurance [10]. Li et al found that knee flexor muscle strength and reaction time were improved after TCC training [8]. Guo et al found that individuals who practiced TCC for many years performed better in balance, ankle proprioception, and knee muscle strength tests than those who did not practice TCC [4].…”
Section: Several Dance Companies In Taiwan Have Introduced Tai Chimentioning
confidence: 99%
See 1 more Smart Citation